Description of a new Moridilla species from North Sulawesi, Indonesia (Mollusca: Nudibranchia: Aeolidioidea)—based on MicroCT, histological and molecular analyses - Schillo, Dorothee; Wipfler, Benjamin; Undap, Nani; Papu, Adelfia; Böhringer, Nils; Eisenbarth, Jan-Hendrik; Kaligis, Fontje; Bara, Robert; Schäberle, Till F.; König, Gabriele M.; Wägele, Heike (Zootaxa, 2019)
We describe a new species, Moridilla jobeli sp. nov., belonging to the marine heterobranch group Aeolidioidea. Up to now, it is only recorded from Bunaken National Park, North Sulawesi, Indonesia. A combination of histological, computer tomographic and scanning electron microscopic methods was applied in order to describe and illustrate the anatomy of Moridilla jobeli sp. nov. in detail. Furthermore, we conducted molecular analyses which include available partial COI and 16S rRNA sequences, as well as the nuclear gene Histone 3 (H3) of Facelinidae and Aeolidiidae. NeighborNet analyses, species delimitation tests and phylogenetic reconstruction methods show the distinctiveness of the new species from the type species Moridilla brockii Bergh, 1888 and the two recently described species Moridilla fifo Carmona & Wilson, 2018 and Moridilla hermanita Carmona & Wilson, 2018, as well as the monophyly of the genus. A phylogenetic analysis of the Facelinidae and Aeolidiidae does not result in a resolved tree, therefore relationship of former assumed closely related genera, Noumeaella Risbec, 1937 and Palisa Edmunds, 1964, cannot be discussed in detail.